Energy-aware joint power and rate control in overlay cognitive radio networks: a Nash bargaining perspective. (1st January 2013) - Yang, Chungang; Sheng, Min; Li, Jiandong; Li, Hongyan; Li, Jing
We investigate a joint energy-aware power and rate control scheme for overlay spectrum sharing cognitive radio networks, and we expect to achieve an optimal performance tradeoff between individual fairness and network energy efficiency. Therefore, a quality of energy efficiency-based Nash bargaining cooperative game (QoE 2 -NBCG) is formulated with the aid of a newly-built 'energy-per-bit' individual utility function in this paper. Mathematically, a multi-constrained optimisation problem is formulated with the novel individual QoE 2 utility function. To reduce the implementation complexity, we utilise decomposition techniques to decouple this multi-constrained problem. Meanwhile, an iterative dynamic bargaining algorithms (IDBA) with limited information exchange is developed based on the derived closed-form of power and rate solutions. In addition, the existence and uniqueness of socially optimal Nash bargaining solutions are validated via theorems. Numerical results verify the convergence of the proposed algorithm, the overall performance improvement and the optimal tradeoff between transmission rate and 'energy-per-bit' efficiency.